CAPACITY BUILDING OF HEALTH CADRES IN 3T AREAS FOR DIGITAL HEALTH TRANSFORMATION - Niko Azhari Hidayat; Fitri Retrialisca; Muhammad Aldo Setiawan; Aditya Putra Pratama Santosa; Diah Khrisma Putriana; Sely Novita (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
Increasing the capacity of health cadres in underdeveloped, frontier, and outermost (3T) areas is a strategic step in supporting digital health transformation in Indonesia. Health cadres as the frontline in health services have an important role in improving access and quality of services in hard-to-reach areas. The purpose of this community service is to increase the knowledge of health cadres about the benefits of digital health, especially telehealth. Efforts to increase knowledge are carried out through organizing workshops for health cadres related to digital health transformation and telehealth utilization as well as socialization and education activities related to the adaptation of digital health technology. Changes in knowledge levels were measured using questionnaires before and after the activity. The targets of the activity amounted to 31 health cadres. The results of the analysis showed an average level of positive change in knowledge with an increase in the knowledge of health cadres (93,5%) in workshop activities and (100%) in socialization and education activities. The results of this activity provide provisions for health cadres to increase their role in utilizing digital health with the knowledge that has been obtained during community service activities. In addition, through this community service activity it is also a reference for policy makers in equalizing digital health transformation and achieving health development targets.